THE PHYSICOCHEMICAL CHARACTERISTICS OF RECYCLED-PLASTIC PELLETS OBTAINED FROM DISPOSABLE FACE MASK WASTES - Vienna Saraswaty; Rossy Choerun Nissa; Bonita Firdiana; Akbar Hanif Dawam Abdullah (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2021)
THE PHYSICOCHEMICAL CHARACTERISTICS OF RECYCLED-PLASTIC PELLETS OBTAINED FROM DISPOSABLE FACE MASK WASTES. The government policy to wear a face mask during the COVID-19 pandemic has increased disposable face mask wastes. Thus, to reduce such wastes, it is necessary to evaluate the physicochemical characteristics of disposable face masks wastes before the recycling process and the recycled products. In this study, physicochemical characterization of the 3-ply disposable face masks and the recycled plastic pellets after disinfection using 0.5% v/v sodium hypochlorite were evaluated. A set of parameters including the characterization of surface morphology by a scanning electron microscope (SEM), functional groups properties by a fourier transform infra-red spectroscopy (FT-IR), thermal behavior by a differential scanning calorimetry (DSC), tensile strength and elongation at break were evaluated. The surface morphological of each layer 3-ply disposable face mask showed that the layers were composed of non-woven fibers. The FT-IR evaluation revealed that 3-ply disposable face mask was made from a polypropylene. At the same time, the DSC analysis found that the polypropylene was in the form of homopolymer. The SEM analysis showed that the recycled plastic pellets showed a rough and uneven surface. The FT-IR, tensile strength and elongation at break of the recycled plastic pellets showed similarity with a virgin PP type CP442XP and a recycled PP from secondary recycling PP (COPLAST COMPANY). In summary, recycling 3-ply disposable face mask wastes to become plastic pellets is recommended for handling disposable face mask wastes problem.